Analysis of the Need for Construction Services towards the Minimum Competency Standards for Vocational Student Work Attitudes - Rolly Robert Oroh (Cita konsultindo, 2023)
This research aims to find the minimum standards of work attitude competency for vocational high school (VHS) students required by construction services in carrying out work on concrete structures. This research uses a descriptive research approach. Research data was collected through surveys, field observations, and focus group discussions with construction service actors. This research was conducted in North Sulawesi province, Indonesia. The participants in this research were 5 construction service actors who were taken randomly from representatives of construction service actors registered with the North Sulawesi provincial construction services development agency. The research data was analyzed for its suitability to construction service needs and Indonesian national work competency standards. The results of the research found that the minimum standard of competency for work attitudes of VHS students which must meet the needs of construction services in carrying out concrete construction work is accuracy and thoroughness in carrying out scaffolding work, concrete molding work, concrete reinforcement work and concrete casting work. This research also found 3 classifications of student work attitude competency achievements according to construction service needs, namely classification A means